Petrogenesis of the Lalezar granitoid intrusions (Kerman Province - Iran) - S. M. Niktabar; A. Moradian; H. Ahmadipour1; J. F. Santos; M. H. Mendes (Journal of Sciences, Islamic Republic of Iran)
The Lalezar granitoids crop out within volcanic successions of the Urumieh-Dokhtar Magmatic Assemblage (UDMA). These granitoids have a range from gabbro-diorites to granites in composition. The mineral compositions of the most felsic rocks are characterized by the abundances of Na-plagioclase, quartz, alkali feldspar, biotite and hornblende. In the gabbro-diorite rocks, plagioclase (Ca-rich), hornblende, biotite and clinopyroxene are the most common minerals. Major element geochemical data show that the Lalezar granitoids are mostly metaluminous, although the most felsic members (granites) attain slightly peraluminous compositions and that they have features typical of high-K calc-alkaline rocks. In primitive mantle-normalized trace element spider diagrams, the analysed samples display strong enrichment in LILE compared to HFSE, accompanied by negative anomalies of Nb, Ta and Ti. REE chondrite-normalized plots show moderate LREE enrichment with slight to strong negative Eu anomalies. Rb–Sr geochronological data, mainly dependent on the Sr isotopic composition of biotite, was obtained in two samples and it points to 15-16 Ma. As a probable, age for the emplacement of the studied intrusives. Initial 87Sr/86Sr ratios and ƐNdi values range from 0.70495 to 0.70565 from +3.1 to +1.5 respectively, which fit into a supra-subduction mantle wedge source for the parental melts and indicates that, in general, crustal contribution for magma diversification was not relevant. Geochemical and isotopic evidence reveal that the Lalezar intrusions are cogenetic I-type granitoids which were generated in a continental arc setting, in agreement with models previously presented in the UDMA.